EFFECTS OF INHALED CORTICOSTEROIDS IN STABLE CHRONIC OBSTRUCTIVE PULMONARY DISEASE : A COMPREHENSIVE SYSTEMATIC REVIEW - Apriyanto, Anggy; Nova, Lusiana (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Inhaled corticosteroids aid COPD patients by improving lung function and reducing exacerbations. The combination of ICS and LABA is more effective than LABA alone, indicating that blood eosinophilia influences therapy efficacy. Patients with low peak inspiratory flow may not receive enough delivery, necessitating the use of spacers to enhance inhaler actuation and inspiration timing. This study aims to systematically review the literature on the effects of inhaled corticosteroids in stable COPD in the last 10 years. Methods: This systematic review used the PRISMA 2020 principles and examined full-text English literature published between 2014 and 2024. Submissions without a DOI were not taken into consideration, nor were editorials and review papers from the same publication. Online resources like PubMed, SagePub, and ScienceDirect were used to compile the literature. Result: Initially, our study team gathered over 60,000 papers from reputable websites such as PubMed, SagePub, and ScienceDirect. Only five papers were found to be directly relevant to our ongoing systematic review after a thorough three-level filtering approach. These publications were then selected for further research through full-text reading. Conclusion: ICS is an effective treatment for COPD because it reduces inflammation, improves airway remodelling, and lowers bacterial load. Higher doses are more effective, because budesonide inhalation enhances lung function.